2022
DOI: 10.21873/anticanres.15814
|View full text |Cite
|
Sign up to set email alerts
|

Intradural Extramedullary Spinal Metastases from Non-neurogenic Primary Tumors: A Systematic Review

Abstract: Background/Aim: Intradural extramedullary spinal metastases (IESMs) may severely affect quality-of-life of oncological patients. Several treatments are available but their impact on prognosis is unclear. We systematically reviewed the literature on IESMs of non-neurogenic origin. Materials and Methods: PubMed, Ovid EMBASE, Scopus, and Web-of-Science were screened to include articles reporting patients with IESMs from non-neurogenic primary tumors. Clinico-radiological presentation, treatments, and outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In addition, one series notes that sensory and motor deficits occur in 58 and 54% of cases, respectively. The same series found that acute cauda equina syndrome is observed in approximately one-third of cases [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one series notes that sensory and motor deficits occur in 58 and 54% of cases, respectively. The same series found that acute cauda equina syndrome is observed in approximately one-third of cases [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the anatomical proximity to spinal nerves or the dura mater, schwannomas, meningiomas, and ependymomas emerge as the predominant primary tumors of the spinal canal [ 5 , 6 ]. Certain malignant primary [ 7 , 8 , 9 , 10 ] or metastatic [ 11 , 12 ] intradural lesions, although infrequent, may resemble their primary counterparts; however, their initial management differs as it typically requires adjunct oncological treatment [ 13 , 14 ]. Among the less commonly encountered non-malignant tumors are ependymomas, hemangiomas, lipomas, paragangliomas, vascular neoplasms, nerve sheath myxoma, and other exceptionally rare entities, including the seldom-described glomus tumors of the spinal canal [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%